THE ADDED WORKER EFFECT IN BRAZIL: : WIFE RESPONSE TO THE HEAD OF HOUSEHOLD’S UNEMPLOYMENT (2012 TO 2017) - Silva, Claudeci; da Cunha, Marina Silva (Análise Econômica, 2023)
When the principal responsible for the family loses his or her job, it is hoped that, in attempting to maintain the level of family income, another member of the family will become part of the workforce; when this occurs, it has an added worker effect. Thus, the objective of this work is to test the hypothesis of the presence of the additional worker effect for the wife when confronting the unemployment of the head of the family in Brazil. Therefore, we used continuous Pnad information from 2012 to 2017 and variations in the specifications of models’ logit for the wife’s transitions into the job market. It was found that the loss of the job of the head of household has a strong effect on the labour supply of the spouse, mainly in the transition from inactivity to unemployment. It was also found that, in addition to the unemployment of the head of the family, there are other factors that explain the transitions of the spouse in the labour market, particularly when small children are present in households. These factors indicated that the lower the age of these children is, the lower the likelihood of wives participating in the labour market.